2022
DOI: 10.3390/nano12224000
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the Study of Vortex Pinning Centers in High-Temperature Superconducting Films

Abstract: Since the discovery of high-temperature superconductors (HTSs), significant progress in the fabrication of HTS films has been achieved. In this review, we intend to provide an overview of recent progress in how and why superconductivity can be enhanced by introducing nanoscale vortex pinning centers. The comprehensive control of morphology, dimension, orientation and concentration of artificial pinning centers (APCs) and the principle of vortex pinning are the focus of this review. According to the existing li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 185 publications
0
6
0
Order By: Relevance
“…Other studies have also explored the introduction of a second phase to enhance pinning performance, demonstrating the potential for significant advancements in superconducting materials. 17,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] Novel methods for second phase doping are also being developed. Recent efforts have aimed to refine the adjustable pinning landscape by controlling the nanoparticle size.…”
Section: Secondary Phase Dopingmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have also explored the introduction of a second phase to enhance pinning performance, demonstrating the potential for significant advancements in superconducting materials. 17,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] Novel methods for second phase doping are also being developed. Recent efforts have aimed to refine the adjustable pinning landscape by controlling the nanoparticle size.…”
Section: Secondary Phase Dopingmentioning
confidence: 99%
“…The morphology, size, orientation, and density of APCs can be meticulously manipulated using various methods. 17 In real-world scenarios, the success of vortex pinning is highly dependent on the microstructure, temperature, and magnetic field conditions. For instance, certain defects may be highly effective at low temperatures but less at higher temperatures or vice versa.…”
Section: Forcementioning
confidence: 99%
See 1 more Smart Citation
“…The property led scientists to search for forms of high-temperature superconductors with stronger current-carrying capacity by articially designing the shape, density and distribution of pinning centers. [24][25][26][27] Related studies have shown that the nanoscale second phase has superior properties J c values as a pinning center for superconductors. In contrast, the effect of doping of Er and Y elements on Bi2212 has rarely been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The value of J c,v can be substantially increased under high-field range by enhancing the vortex pinning via introduction of artificial pinning centers (APC) within the superconducting lattice [6]. This is typically done by adding a non-superconducting dopant material within a bulk superconductor and using it as a target for thin film manufacture via pulsed laser deposition (PLD).…”
Section: Introductionmentioning
confidence: 99%